Integrating Halal Nutraceutical Product Development with Religious Mentoring in a Convert-dominant Farming Community - Zainal Arifin; Junaidi, Junaidi; Moh Holil Baitaputra; Mufaizin, Mufaizin; M. Tohir (Journal of Community Service and Engagement, 2026)
In a convert-dominant Muslim community surrounded by a Christian majority in rural East Java, Indonesia, organic vegetable farmers face two intersecting challenges: low economic value from unprocessed produce and weak religious mentoring due to economic pressures. This community empowerment study aimed to integrate halal nutraceutical product training with Islamic religious mentoring to enhance both entrepreneurial skills and religious participation among 10 female farmers from the "Ngudi Rahayu" organic farming group. Using a group-based participatory action research design over three months (June–August 2021), the intervention included socialization, production training for organic vegetable chips, packaging and marketing under Islamic principles, and weekly religious mentoring. Data were collected through observation, in-depth interviews with community and religious leaders, and documentation of program outputs. Results showed that all 10 participants developed entrepreneurial competencies, successfully produced halal-certifiable vegetable chips, and actively engaged in religious activities with support from local mosque leaders and the district office of religious affairs. Stakeholders, including the village head and youth organization leader, reported high enthusiasm and perceived improvements in both economic and religious resilience. The study concludes that simultaneously addressing economic and religious needs is feasible and effective for convert communities. The implication is a novel integrative empowerment model the Halal Empowerment Model for Convert Communities (HEMCC)—that combines halal nutraceutical entrepreneurship with sustained religious mentoring. This model offers a replicable framework for community development programs in minority-religion contexts.